Birthplace of Dashehari mango: Introduction brief on Dashehari mango - Sthapit, S.; Ravishankar, H.; Reddy, B.M.C.; Rajan, S. (2010)
Dashehari’ is one of the most popular mango varieties of North India. It is widely acclaimed for its exquisite taste and pleasant aroma. It is believed that 80% of all mango varieties in Malihabad (North India) is covered by ‘Dashehari’ and they can be genetically traced back to this very tree. The UNEP/GEF-funded project ‘Conservation and sustainable use of wild and cultivated fruit tree diversity: Prompting Sustainable Livelihoods, Food Security and Ecosystem Services’ aims to empower farming communities and local institutions in Malihabad, Lucknow, North India, for identifying unique varieties from the orchards and scaling up genetic resources and associated traditional knowledge for sharing wider benefits to farmers and consumers.